Female Farmers’ Knowledge as the Start-Up Capital for an Agribusiness Incubator: A Perspective of Banyubiru Village, Semarang Regency, Central Java, Indonesia - Kuswardinah, Asih; Ansori, Muhammad; Rachmawati, Rina; Fajri, Mediati Putri (Nurture, 2021)
Most of the members of the Female Farmer Group (FFG) in Banyubiru, Semarang regency have a low educational level and a weak socio-economic status. Related to that, the purpose of this research is to find out whether the women’s entrepreneurship knowledge can be the main capital in their readiness for the establishment of an agribusiness incubator; and whether the results of the Strength- Weakness-Opportunity-Threats (SWOT) analysis support the feasibility and urgency for Banyubiru village to establish an agribusiness incubator. This research applied a one-shot case study in which the female farmers were subject to three interventions. Data on the women’s entrepreneurship knowledge was collected through various measuring instruments, while data for the SWOT analysis was obtained through two Focus Group Discussion (FGD). The research subjects were women farmers, FFG administrators, farming trainers and village officials. A sample of 198 female farmers was determined by snowballing technique from 440 active FFG members. Research was carried out in Banyubiru village, Banyubiru sub-district, Semarang regency, Central Java, Indonesia. Through this research, it was found that 1) female farmers’ entrepreneurship knowledge could be the main capital for their readiness to pioneer an agribusiness incubator; 2) the results of the SWOT analysis on the modality factors determined that it was feasible and considered to be urgent to establish an agribusiness incubator in Banyubiru village. This research conclusively confirms that it is very feasible and considered to be urgent to establish an agribusiness incubator in Banyubiru village in Banyubiru sub-district.